Endocrine Disrupting Chemicals - Harrison, R. M; Hester, R. E (Issues in environmental science and technology, 1999)
Long-term environmental effects of chemical exposure have long been of concern and, more recently, chemicals which cause changes to the sexual development of exposed organisms have been identified. It is thought that low-level exposure to a range of chemicals may be affecting endocrine function, leading to a reduction in fertility and an increase in reproductive cancers. This 12th volume of Issues in Environmental Science and Technology reviews the scientific evidence and attempts to put the subject into context. Along with an overview of the issue, there is discussion of the specialised aspects in relation to wildlife; environmental oestrogens and male reproduction; and naturally occurring oestrogenic substances.